Comparison of Genetic Merit for Weight and Meat Traits between the Polled and Horned Cattle in Multiple Beef Breeds - Randhawa, Imtiaz A. S. (Animals (Basel), 2021)
SIMPLE SUMMARY: Beef production has expanded worldwide through cattle adaptation to diverse environmental and husbandry conditions. The beef industry faces societal challenges from animal welfare perspectives, including dehorning and disbudding, which are common farm practices to limit animal and handler injuries by the horned cattle. Most cattle breeds were originally horned, and reluctance to poll breeding existed because of perceived negative correlations between polledness and production. In Australia, population trends indicate a recent rise to above 50% of poll types in six breeds (Charolais, Hereford, Limousin, Simmental, Shorthorn, and Droughtmaster), and two breeds with lower but increasing rates of polledness (Brahman and Santa Gertrudis). Overall, recently estimated breeding values of 12 investigated production traits have not shown consistently negative trends within and across breeds. Thus, polledness should not be considered as detrimental. Cautious breeding plans are warranted to avoid inbreeding depression in breeds with lower poll frequency. These findings should support the augmented poll breeding across the beef industry. ABSTRACT: Breeding for polled animals is deemed the most practical solution to eradicate horns naturally and circumvent management costs and risks on health and welfare. However, there has been a historical reluctance by some farmers to select polled animals due to perceived lower productivity of their calves. This study has compared estimated breeding values (EBVs) between horned and polled animals (N = 2,466,785) for 12 production and carcass traits to assess historical (before 2000) and recent (2000–2018) genetic implications of poll breeding. Older generations of the polled animals in most breeds had significantly lower (Bonferroni-corrected p = 0.05) genetic merits for live (birth to maturity) and carcass weights, milk, meat quality, and fat content traits. Substantial gains of genetic potential were achieved during 2000 to 2018 in each breed, such that polled animals have significantly improved for the majority of traits studied. Generally, polled cohorts showed advantageous EBVs for live and carcass weights irrespective of the lower birth weights in some breeds. While Polled Brahman showed inferior production parameters, the poll genetics’ effect size (d) and correlation (r) were very small on recent birth weight (d = −0.30, r = −0.08), 200 days (−0.19, −0.05), 400 days (−0.06, −0.02), 600 days (−0.05, −0.01), mature cow live weight (−0.08, −0.02), and carcass weight (−0.19, −0.05). In conclusion, although there is some evidence that historical selection for polled breeding animals may have reduced productivity, there is strong evidence that more recent selection for polled genotypes in the breeds studied has not resulted in any adverse effects on genetic merit.